2020
DOI: 10.1101/2020.11.17.386458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective vulnerability of supragranular layer neurons in schizophrenia

Abstract: Schizophrenia is one of the most wide-spread mental brain disorders with complex and largely unknown etiology. To characterize the impact of schizophrenia at a cellular level, we performed single nucleus RNA sequencing of >190,000 neurons from the dorsolateral prefrontal cortex of patients with schizophrenia and matched controls (7 vs 11, respectively). In addition, to correlate data with cortical anatomy, >100,000 neurons were analyzed topographically by immunohistochemistry in an extended cohort of cas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…We hypothesize that the differences we observe may be due to an altered plasticity mechanism of reinforcing certain neuronal connections during neurodevelopment, resulting in fewer different configurations strengthened in the SZ condition. This possibility is supported by the fact that genome wide-association studies [49][50][51] and a recent singlenucleus RNA sequencing (snRNAseq) analysis in SZ [52], have evidenced alterations in sequence and expression of several genes implicated in specific synaptic pathways related to plasticity [53].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the differences we observe may be due to an altered plasticity mechanism of reinforcing certain neuronal connections during neurodevelopment, resulting in fewer different configurations strengthened in the SZ condition. This possibility is supported by the fact that genome wide-association studies [49][50][51] and a recent singlenucleus RNA sequencing (snRNAseq) analysis in SZ [52], have evidenced alterations in sequence and expression of several genes implicated in specific synaptic pathways related to plasticity [53].…”
Section: Discussionmentioning
confidence: 99%
“…Using simple MDS plots and tests, we indeed found that in many cases batch or other technical factors drove expression or compositional differences of the datasets more than the conditions the study was designed to compare. Especially when unbalanced, such factors can significantly distort the results, highlighting the importance of tracking and testing for association with technical and design factors, as was done for instance in (Batiuk et al, 2020). Further methodological developments will be needed to incorporate ability to control and correct for extraneous factors within the comparison tests themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the disease in different samples, however, may be heterogeneous, and result in shifts of disease samples along different directions, effectively increasing variability of the expression states in the disease condition ("variance change", Fig. 4C,F) (Batiuk et al, 2020). Such situation is likely to be characteristic of complex spectrum disorders, such as schizophrenia and autism, where understanding of multidirectionality of transcription shifts could help to distinguish subgroups of patients.…”
Section: Cluster-based Expression Shiftsmentioning
confidence: 99%
“…Our findings of SCZ-associated changes in upper-layer neurons were validated by multiple lines of experiments from other studies. In a recent snRNA-seq study of cortical layers from seven SCZ patients and 11 controls, the selective vulnerability of supragranular layer neurons was revealed in SCZ in terms of dramatic transcriptomic changes and cell proportion changes 47 . A decreased proportion of upper-layer neuron subtypes was also observed in mouse model SCZ-predisposing 22q11.2 microdeletion 48 and human postmortem brains 49,50 .…”
Section: Discussionmentioning
confidence: 99%